Direct laser interference patterning of ophthalmic polydimethylsiloxane (PDMS) polymers. (July 2018) - Sola, D.; Lavieja, C.; Orera, A.; Clemente, M.J.
Highlights: Direct laser interference patterning technique of polydimethylsiloxane polymers is reported. Linear line-like patterns produced on the samples are studied. Compositional and microstructural characterization is carried out. Diffraction gratings were studied to assess the refractive index modification. Refractive index change one order of magnitude higher than in the ULI technique was obtained. Abstract: The inscription of diffractive elements in ophthalmic polymers and ocular tissues to induce refractive index changes is of great interest in the fields of Optics and Ophthalmology. In this work fabrication of linear periodic patterns in polydimethylsiloxane (PDMS) intraocular lenses by means of the direct laser interference patterning (DLIP) technique was studied. A Q-Switch Nd:YAG laser coupled to second and third harmonic modules emitting linearly polarized 4 ns pulses at 355 nm with 20 Hz repetition rate was used as the laser source. Laser processing parameters were modified to produce the linear patterns. Processed samples were characterized by means of optical confocal microscopy, Scanning Electron Microscopy SEM, Energy Dispersive X-ray Spectroscopy EDX, Attenuated Total Reflectance-Infrared Spectroscopy ATR-FTIR, and Raman Spectroscopy. Depending on the laser parameters both photo-thermal and photo-chemical damage were observed in the DLIP irradiated areas. Finally, diffractive techniques were used to characterize the diffraction gratings inscribed in the samples resulting in a refractive index change of 1.9 × 10 −2 under illumination of a 632.8 nm He-Ne laser.